Possibilities of ICT in hospital classrooms - Mª Paz Prendes Espinosa; Mª del Mar Sánchez Vera; José Luis Serrano Sánchez (Universidad de Granada, 2012)
The investigation presented has a conclusion of improving the educative attention that children who find themselves in the care of hospital receive during considerable amount of time (and that during this period, they attend classes overseen by the hospital) through the use of ICT and the design and validation a network protocol, which is based on the use of telematics tools Web 2.0. After undergoing the investigations and experiments related to the topic, we come to the conclusion that in the majority of cases, the playful use of ICT in the hospital classrooms dominates the educative. This educative experiment originates from the collaboration between investigators from different universities, experts in educative technology and the teaching staff from hospital classrooms in the region of Murcia. In this assignment we present the actions taken, the phase in which right now we find the project and the actions yet to be completed.